The Correlation Between Watching Television and Bodily-Kinesthetic Intelligence of 6 Years Old Children - Fadhli, Muhibuddin; Utami, Prihma Sinta (Universitas Negeri Semarang, 2018)
The aim of this research is to find out the correlation between duration of watching television and bodily-kinesthetic intelligence of 6 years old. Six development scopes according to Regulation of National Education Minister of Indonesia Number 137 in 2014, what must be stimulated in accordance with the achievement level of six years old childrenâ€™s development cover language, art, physical, social emotional, cognitive, moral, and religion. Bodily-kinesthetic or physical ability, according to Gardner, becomes one of competences that must be developed at early age. The research method used was quantitative research. The analysis was done by using correlation product moment with two variables; independent variable which is the duration of watching television (variable X) and dependent variable which is bodily-kinesthetic intelligence (variable Y). The decision criteria if â€œrâ€ score (r count) along with significance (sig.) <0,05, then independent variable has strongly convincing correlation with dependent variable. If â€œrâ€ score (r count) along with significance (sig.) > 0,05, then the independent variable has strongly convincing correlation with the dependent variable. The results of the research showed correlation coefficient (r) = 0,842 along with significance 0,000. Based on the decision criteria above, it can be concluded that correlation from both variables is significant because its significance is smaller than 0,05 (0,000 < 0,05). Then in can be concluded that there is strong correlation, in which the longer the children watch television then the higher their bodily kinesthetic intelligence was.